PHYLOGENETIC RELATIONSHIP AMONG SELECTED SPECIES OF LAMIACEAE INFERRED FROM CHLOROPLAST RPS14 GENE - A. Malik1; T. Shahzad; S. Arif; W. Akhtar; T. Mahmood (Journal of Animal and Plant Sciences, 2020)
The Lamiaceae is commonly known as Mint family of order Lamiales. The present study was conducted for assessment of genetic diversity, phylogeny of Lamiaceae based on rps14 gene and validation of rps14 protein by Ramachandran plots. The rps14 gene was amplified and sequence analyzed through MEGA7, I-TASSER and RAMPAGE. The phylogram revealed genetic distance (number of base substitutions per site) of 0.0100 among Lamiaceae species. In Pairwise distance, the range of genetic diversity was 0.013 to 0.089 with a mean of 0.060. Vitex agnus castus and Vitex trifolia were grouped in same cluster with Bootstrap value of 99 %. Caryopteris odorata revealed close relationship with Volkameria inermis, Clerodendrumcalamitosum and Clerodendrum indicum in same cluster having BS of 58 %. C. indicum, C. calamitosum and V. inermis showed close relationship in same cluster with BS of 51%. The 3D protein model designed by I-TASSER and its validation by RAMPAGE revealed ≤ 2 % amino acid in outlier regions of Gmelina philippensis, Clerodendrum. umbellatum and C. calamitosum. This study concluded close genetic relationship and low genetic diversity that indicated potential of rps14 gene for phylogeny and diversity analysis among Lamiaceae species. The validation of 3D protein models by RAMPAGE showed good protein models. This study highlights the evolutionary relationship, earliest, recent evolution of Lamiaceae species. A very low genetic diversity indicates ex-situ conservation and good protein models in Lamiaceae species.
Keywords: Lamiaceae; Iterative Threading Assembly Refinement; rps14 gene; Pairwise distance; Genetic diversity